2007
DOI: 10.1111/j.1600-0501.2007.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the 5‐year survival and complication rates of implant‐supported single crowns

Abstract: OBJECTIVES: The objective of this systematic review was to assess the 5-year survival of implant-supported single crowns (SCs) and to describe the incidence of biological and technical complications. METHODS: An electronic MEDLINE search complemented by manual searching was conducted to identify prospective and retrospective cohort studies on SCs with a mean follow-up time of at least 5 years. Failure and complication rates were analyzed using random-effects Poisson's regression models to obtain summary estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
703
13
62

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 905 publications
(856 citation statements)
references
References 36 publications
32
703
13
62
Order By: Relevance
“…From a biomechanical perspective, previous in vitro studies [12][13][14][15][16][17] have shown reduced levels of stress on peri-implant bone in platform-switched implants relative to matched implant-abutment diameters. Such potential for crestal bone level preservation has been shown in animal [18][19][20] and clinical studies [11,21,22].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…From a biomechanical perspective, previous in vitro studies [12][13][14][15][16][17] have shown reduced levels of stress on peri-implant bone in platform-switched implants relative to matched implant-abutment diameters. Such potential for crestal bone level preservation has been shown in animal [18][19][20] and clinical studies [11,21,22].…”
Section: Introductionmentioning
confidence: 89%
“…On the other hand, complications with implant-abutment connections is still a common clinical problem, especially in single-tooth replacements [18,23,24]. When considering platform-switched implants, previous studies [14,17] have shown an increased stress on the abutment and fixation screw, which may compromise the system biomechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…3,14,15 A lack of keratinised mucosa does not appear to be associated with an increased incidence of peri-implantitis. 13 Jung et al 2 reported that 6.3% of implant supported single crowns had bone loss >2 mm over a 5 year observation period. Pjetursson et al 7 reported that less than 8.6% (95% CI; 5.1%-14.1%) of implant supported fixed partial dentures were affected by peri-implantitis over 5 years.…”
Section: Peri-implantitismentioning
confidence: 99%
“…1 Systematic reviews have reported relatively high survival rates for dental implants supporting crowns 2 and fixed bridgework. [3][4][5][6][7] However, these reviews have also identified a variety of complications that may be associated with these prostheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation